Identification of International Human Rights Principles in Indonesia’s New Criminal Code - Saputro, Muhammad Eko; Mukhoyyaroh, Vina Durrotul; Febrianti, Ayu; Tahir, Mohammad Saleh; Arifin, Ridwan; Latifiani, Dian (Law Research Review Quarterly, 2023)
This paper explores the incorporation and alignment of international human rights principles within Indonesia's latest Criminal Code. As nations strive to uphold fundamental rights and liberties, examining the compatibility of domestic legislation with international standards is imperative. This study employs a comprehensive analysis of Indonesia's new Criminal Code, focusing on the identification and assessment of provisions that either conform or diverge from established international human rights norms. By scrutinizing key legal aspects, such as due process, freedom of expression, and protection against discrimination, this paper aims to shed light on the extent to which Indonesia's legal framework reflects its commitment to global human rights standards. The findings contribute valuable insights into the ongoing discourse surrounding the harmonization of domestic laws with international human rights instruments, offering implications for policy development, legal reform, and fostering a culture of respect for human rights in Indonesia.